The use of the graded response model (GRM) in the process of the assessment of the psychological content of work among employees - Molek-Winiarska, Dorota; Zięba, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
Purpose: the objective of this paper is to analyze the possibility of the use of GRM in evaluating the psychological content of the work among employees. Design/methodology/ approach: the study was conducted on a sample of 500 employees in a mining company with the use of a standardized JCQ questionnaire by R. Karasek. The study is based on adapting existing scientific theories, according to which GRM is used for the purpose of solving problems, combined with the application of the GRM for the analysis of empirical material. Findings: the findings and comparisons show that the GRM can be useful in the employee assessment process. The model allowed to find relevant differences between employees who achieved the same results in JCQ. This led to establishing a valid diagnosis in employee’s resources and demands. Furthermore, it can be claimed that, in some cases, more detailed solutions were obtained with the use of the GRM, facilitating in a further stage making decisions and planning actions in order to identify the factors determining the improvement of working conditions and affecting employee motivation. Implications: in the presented study, the GRM was used for an in-depth analysis of job content and employee resources as diagnosed by Karasek’s JCQ. In the second part of the article the results were applied to suggest a better organization of work to facilitate the development of individual potential. The ideas were successfully implemented during the work-related health promotion program in the company. Originality/value: such an analysis is rarely considered in the literature. It can provide useful information about employee performance and potential
Argumenta Oeconomica, 2019, Nr 1 (42), s. 295-315
Keywords: GRM; latent trait model; employee potential; psychological content of work; Karasek